The case of the cryptic crinoline - Springer, Nancy (Springer, Nancy. Enola Holmes mystery, 2011)
In late nineteenth-century London, fourteen-year-old Enola Holmes, much younger sister of detective Sherlock Holmes, turns to Florence Nightingale for help when her investigation into the disappearance of a Crimean War widow grows cold.